МЕҲНАТ РЕСУРСЛАРИ ВА УНДАН ФОЙДАЛАНИШ (Сурхондарё вилояти мисолида) - Тожиева, З.Н.; Пардаев, Н.С.; Хурсанов, С.М. (SCIENCE and SOCIETY, 2024)
The article describes the growth of labor resources of Surkhandarya region and its structural changes, the employment of economically active and inactive population in the labor resources, and the level of unemployment.